Analisis Strategi Pengembangan Usaha Wedang Jahe Instan Jawaru di Kabupaten Garut - Rd. Putry Mentari Aeni; Tatang Mulyana; Muhamad Nu’man Adinasa (Ma'soem University, 2022)
Wedang Jahe Instant Jawaru is a traditional health drink ginger-based produced by UMKM Jawaru. This study aims to identify the company's internal and external factors, and identify the best strategy that can be applied to the development of UMKM Jawaru in Pasirwaru Village, Blubur Limbangan District, Garut Regency. The research method used is a qualitative and quantitative method for 10 key informants. Internal factors include strengths and weaknesses from within the company consisting of management, production and operations, finance, marketing, and human resources, while external factors include opportunities and threats from outside the company consisting of economic, social & cultural, political, policy, legal, technology and competitors. The results showed that the internal factor that became the strength of the UMKM Jawaru was the quality of the product with a score of 0.43, as well as the internal factor that became a weakness was control management with a score of 0.14, while the external factor that became an opportunity was the rapid development of the internet with a score of 0.68, as well as external factors that pose a threat was competition with products that have been around for a long time with a score of 0.24, and there are 8 alternative strategies resulting from the development of the SWOT strategy types that can be applied in UMKM Jawaru.